A spherical lattice shell composed of six-bar tetrahedral units: Configuration, structural behavior, and prefabricated construction. Issue 7 (July 2016) - Dong, Shi-lin; Bai, Guang-bo; Zheng, Xiao-qing; Zhao, Yang
A novel spherical lattice shell composed of six-bar tetrahedral units whose horizontal projections are quadrilaterals is proposed. The lattice shell provides an advantage in industrialized production and prefabricated construction by comprising a plurality of similarly shaped modular units. Kinematic analysis for the lattice shell, based on which several strengthening structures and joint rigidity arrangements are proposed, is carried out. The structural behavior of a basic structure of the lattice shell, whose chord and web members are designed as beam and bar elements, respectively, is studied systematically. Construction details of the nodal joints and six-bar tetrahedral modular units are suggested, followed by a discussion about the construction scheme. A tool called A-shaped installing frame is designed to realize the prefabricated construction without scaffold. A test model of 10-m span was built to verify the feasibility of the nodal joint construction as well as the prefabricated construction scheme.